High reproducibility of spleen stiffness measurement by vibration‐controlled transient elastography with a spleen‐dedicated module. Issue 11 (9th September 2022) - Rigamonti, Cristina; Cittone, Micol Giulia; Manfredi, Giulia Francesca; Sorge, Andrea; Moia, Riccardo; Patriarca, Andrea; Donato, Maria Francesca; Gaidano, Gianluca; Pirisi, Mario; Fraquelli, Mirella
Abstract: Spleen stiffness measurement (SSM) by vibration‐controlled transient elastography (VCTE) is a noninvasive technique for estimating portal hypertension in patients with chronic liver disease (CLD), with its reproducibility yet to be established and its feasibility still unknown beyond CLD. We have studied 420 participants from two tertiary referral centers for liver diseases (Novara, Milan): 297 patients with CLD (32% with cirrhosis) of different etiology (Group A), 63 Philadelphia‐negative myeloproliferative neoplasms (Group B), and 60 heathy volunteers (Group C). All underwent SSM by VCTE with a spleen‐dedicated module (SSM@100 Hz) and liver stiffness measurement (LSM), blindly performed by 2 different operators. In total, 1680 VCTE examinations for SSM were performed (1000 in Novara, 680 in Milan), with an overall 3.2% failure rate. Median SSM was 26.5 kPa (interquartile range [IQR] 20.0–42.3) in Group A, 26.3 kPa (IQR 22.3–33.6) in Group B, and 16.1 kPa (IQR 14.6–18.7) in Group C. In Group A, the median LSM was 6.8 kPa (IQR 4.9–11.3) in Novara and 8.3 kPa (IQR 7.1–10.8) in Milan, the proportion of patients with cirrhosis being 34% in Novara and 31% in Milan. The Group A interobserver agreement ICC was 0.90 (0.88–0.92), significantly lower in the absence of splenomegaly (ICC 0.87 vs. 0.91) and in absence of cirrhosis (ICC 0.84 vs. 0.90); overweight slightly, but not significantly reduced the interobserveragreement. The intra‐observer agreement ICC ranged from 0.91 to 0.96 for the four operators. The Group B interobserver agreement ICC was 0.90 (0.83–0.94). In conclusion, SSM measured by the new spleen‐dedicated VCTE module is a feasible, reliable, and highly reproducible tool in patients with CLD and hematological disorders, and in healthy volunteers. Abstract : Spleen stiffness measurement by VCTE with the new spleen‐dedicated module is a feasible and highly reproducible technique in patients with chronic liver disease, haematological disorders and healthy volunteers with excellent inter‐ and intra‐observer agreement. Being not significantly influenced by overweight or obesity, the technique is largely applicable in different clinical contexts.image